ANALISIS AKUNTANSI PAJAK PENGHASILAN PPH PASAL 22 PADA PT. AYU BUMI SEJATI LABUHAN DELI - Chintya Anggreni; Purwita Sari (Jurnal Widya, 2024)
This research aims to find out the procedures for calculating and collecting, paying and reporting as well as implementing PPh Article 22 accounting and knowing the application of PPh Article 22 accounting at PT. Ayu Bumi Sejati Labuhan Deli. The benefit of this research is to increase researchers' insight into the procedures for calculating and collecting, paying and reporting as well as the application of PPh Article 22 accounting. This research uses a qualitative research type with a descriptive approach. Qualitative descriptive research is aimed at describing and illustrating existing phenomena, both natural and human engineered, which pays more attention to the characteristics, quality, and interrelationships between activities. This research was conducted at PT. Ayu Bumi Sejati Labuhan Deli. Data collection techniques use interviews. The advice I gave in research on the company PT. Ayu Bumi Sejati Labuhan Deli Improves the strategy or motivation system, especially related to the export of manufactured goods in order to increase exports every month or year.